ICT Skills Acquisition and Utilization Among Postgraduate Students in Universities in Kwara State, Nigeria - Olaifa, Adeseko sunday; Adisa, Taofiq Adesola; Are, Seyi; Adeoye, Moses Adeleke; Ayoku, Oba Baba (Universitas PGRI Semarang, 2024)
This study investigates the ICT skills utilization among postgraduate students in Universities in Kwara State, Nigeria. The research design was a descriptive survey of the correlational type. A proportional random sampling technique was adopted to select 250 respondents from the 580 postgraduate students of the Faculties of Education of the selected Universities in Kwara State, Nigeria. The Instrument titled ICT Skills Acquisition and Utilization Questionnaire (ICTSAUQ) was used for data collection. The instruments were validated by experts in the Department of Educational Management and Counselling and found reliable with a reliability coefficient of 0.82. Three research questions were raised for the study and answered using descriptive statistics of mean and standard deviation. One research hypothesis formulated was tested using inferential statistics of Pearson Product Moment Correlation (PPMC) Statistics at a 0.05 level of significance. The findings of this study revealed that there is a significant relationship between the Acquisition of ICT skills and usage among postgraduate students in universities in Kwara State. Based on the findings the study recommends among other things that postgraduate students of Universities in Kwara states should undergo a compulsory ICT skill acquisition skill to aid their academic activities.